Chemotherapy of tumors trophoblast - Solidoro, Andrés (2015)
Chemotherapy of tumors of trophoblast has been successful in several ways. From a practical standpoint, it has allowed for the first time healing a malignant tumor with the use of chemical agents, changing the poor prognosis that had chorioepithelioma less than a decade. From the point of view of tumor biology, it has provided an opportunity to study the tumor guest relations on a "grafted" neoplasia in humans. From the biochemical point of view, it has proven the importance of certain metabolites in a selective way some cancers. The epidemiology and natural history of corioncarcinoma also been studied with renewed interest after advenimento of this therapy.